Five discoveries of Volodymyr Betz. Part one. Betz and the islands of entorhinal cortex: Correction to: Five discoveries of Volodymyr Betz. Part one. Betz and the islands of entorhinal cortex 05.01.2024 - Мedvediev Volodymyr; Cherkasov , Viktor; Vaslovych , Viktoria; Tsymbaliuk , Vitaliy (The Ukrainian Scientific Medical Youth Journal, 2023)
in the series of publications, which this article opens, we consider five fundamental neu- romorphological observations of our compatriot, the classic of world neuroscience, Volodymr Betz. For four of them, we demonstrate the status of discoveries for the first time, for the other one — the giant pyramidal neurons of the motor cortex — despite its widespread and long-standing recognition, we reveal the limitations of modern knowledge and ideas. Two of the mentioned observations — giant fusiform, or spindle-shaped neurons of the cingulate and insular cortex and islands of the entorhi- nal cortex — are currently known only to a narrow circle of specialists; to the others two, cytoarchitectonic description of the olfactory tubercle and some sings of the modular cortex organization, we pay attention for the first time. In this, the initial part of the series, exposing modern apprehensions about the structure and functions of the entorhinal cortex, we demonstrate the weight of Betz’s pioneering observation of extraordinary neu- ron clusters, which are nowadays known as entorhinal islands, and prove the fact of recognizing his historical priority in the description of these amazing brain structures.